Hijacking cellular garbage cans - Welsch, Sonja; Krijnse-Locker, Jacomine (Cell host and microbe, 2010)
Viruses are perfect opportunists that have evolved to modify numerous cellular processes in order to complete their replication cycle in the host cell. An article by Reggiori and coworkers in this issue of Cell Host & Microbe reveals how coronaviruses can divert a cellular quality control pathway that normally functions in degradation of mis-folded proteins to replicate the viral genome.